Participation, Neoliberalism and Depoliticisation of Public Action - Moini, Giulio (SocietàMutamentoPolitica, 2017)
The article argues that political elites – using participation as tools for depoliticisation strategies – seek to obtain the trust of the economic elite and, at the same time, to shield policy making from the unpopular consequences of neoliberal policies. In order to test this hypothesis a specific case of participatory processes, developed in Rome between 2014-2015 is considered.